Citizens Lawsuit: Development And Its Implementation In Environmental Law Enforcement In Indonesia (Case Study: High Court Decision No. 549/Pdt/2022/PT DKI Concerning Citizens Lawsuit for DKI Jakarta Air Pollution) - Uz Zaman, Muhamad Nafi (Universitas Negeri Semarang, 2023)
Citizen lawsuit as a form of lawsuit in enforcing environmental law has already been applied several times in judicial practice in Indonesia. However, the citizen lawsuit mechanism does not yet have specific rules, so the detailed provisions have not been determined either. This raises questions about the development and application of citizen lawsuits in environmental law enforcement in Indonesia and their relevance to citizen participation in environmental preservation. This paper aims to analyze and provide an overview of the challenges and opportunities for citizen lawsuits in Indonesia by taking into account existing practices. The results of the study show that citizen lawsuits are a concrete form of public participation in enforcing environmental law, because they are based on the public interest. In addition, there are challenges to implementing citizen lawsuits that must be studied in more depth, including: the scope which is still limited in the absence of regulations or negligence of government action, the maximum period of time when CLS can be filed, the effect of government lawsuits/indictments on matters being sued in CLS and the executive power of the CLS decision.